(untitled) (World Bulletin of Public Health, 2025)
This article discusses the content, basic principles and importance of the concept of sustainable marketing in the modern economy. The strategic directions of sustainable marketing, its impact on consumer behavior and the problems of its implementation are analyzed. The future prospects of sustainable marketing and its role in the sustainable development of society are also substantiated.